Fetal neuromaturation in late gestation is affected by maternal sleep disordered breathing and sleep disruption in pregnant women with obesity. Issue 1 (17th June 2021) - DiPietro, Janet A.; Watson, Heather; Raghunathan, Radhika S.; Henderson, Janice L.; Sgambati, Francis P.; Pien, Grace W.
Abstract: Objective: Maternal sleep disordered breathing and sleep disruption have adverse effects on pregnancy outcomes through multiple potential pathophysiologic pathways. We hypothesize that disordered maternal sleep also adversely impacts the neuromaturation of the fetus. Methods: Participants in this prospective observational study included 102 obese pregnant women (pre‐pregnancy body mass index [BMI] of 30 or higher) at 36 weeks of pregnancy. Fetal neuromaturation, defined through measures of fetal heart rate variability, motor activity, and motor‐cardiac coupling, was quantified through digitized fetal actocardiography during an afternoon recording. Maternal sleep measures were collected overnight through polysomnography. Data analysis focused on multiple regression, controlling for maternal BMI, blood pressure, and diabetes. Results: Indicators of higher sleep disordered breathing were associated with delayed fetal neuromaturation and greater fetal motor activity. Less maternal sleep disruption (shorter rapid eye movement [REM] latency, more REM sleep, and/or fewer transitions) was associated with higher fetal heart rate variability and coupling‐based neuromaturation. Conclusion: Characteristics of disordered maternal sleep affect the developing fetal nervous system. It is unknown whether these results extend to populations that are not characterized by obesity. The influence of maternal sleep on the developing fetal nervous system has been understudied and may yield effects that persist beyond pregnancy. Abstract : Maternal sleep disordered breathing and sleep disruption adversely affect fetal neuromaturation in pregnant women with obesity.